Analysis of Progressivity of Qawaidh Fiqh Applications on Fatwa DSN-MUI 2017-2021 - Nadiyah Mu’adzah (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
This study seeks to describe how the implementation of the use of fiqh rules contained in the DSN-MUI fatwa for the 2017-2021 period. The study also seeks to describe the factors behind the conclusions of the analysis results obtained. This research uses qualitative methods with a normative juridical approach and descriptive analysis techniques. Review documents in the form of fiqh rules in the 2017-2021 DSN MUI fatwa and literature studies as the most dominant data collection technique used. In addition, interviews with academics and practitioners of DSN-MUI were also conducted in order to obtain more comprehensive and systematic research results. The results of this study found that of the 32 fatwas issued by the DSN-MUI in the 2017-2021 period, there were 152 fiqh rules applied by the DSN-MUI in formulating fatwas as one of the sources of ijtihad. However, of the 152 rules, there are essentially only 30 different fiqh rules used. Each of the rules is repeated several times, only 4 fiqh rules of which are not repeated. In terms of progressivity, in general, the application of qawaidh fiqh in the DSN-MUI fatwa in 2017-2021 has indicated a better increase compared to previous years. But on the other hand, the use of qawaidh fiqh al-'ammah in the DSN-MUI fatwa (2017-2021) is still more than the use of qawaidh fiqhh al-khassah with a ratio of 17:10. These things are due to the presence of certain factors that have been presented in this study.